Metal organic frameworks with carbon black for the enhanced electrochemical detection of 2,4,6-trinitrotoluene - Javaid, Shaghraf; Azhar, Muhammad; Li, Xinyu; Phillips, Juliette; Hussain, T.; Abid, Hussein; Chen, J.; Ji, X.; Silvester-Dean, Debbie (2023)
The sensing of explosives such as 2,4,6-trinitrotoluene (TNT) directly at an explosion site requires a fast, simple and sensitive detection method, to which electrochemical techniques are well suited. Herein, we report an electrochemical sensor material for TNT based on an ammonium hydroxide (NH4OH) sensitized zinc-1,4–benzenedicarboxylate Zn(BDC) metal organic framework (MOF) mixed with carbon black on a glassy carbon electrode. In the solvent modulation mechanism, by merely changing the concentration of NH4OH during synthesis, two Zn(BDC) MOFs with novel morphologies were fabricated via a hydrothermal approach. The as-prepared MOFs were characterized using X-ray powder diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and high-resolution field emission electron microscopy (FESEM) equipped with energy dispersive X-ray spectroscopy (EDS). The different morphologies of the MOFs, and their impact on the performance of the modified electrodes towards the electrochemical detection of TNT was investigated. Under optimum conditions, 0.7–Zn(BDC) demonstrated the best electrochemical response for TNT detection using square wave voltammetry (SWV) with a linear calibration response in the range of 0.3–1.0 μM, a limit of detection (LOD) of 0.042 μM, a limit of quantification (LOQ) of 0.14 μM and a high rate of repeatability. Atomic-scale simulations based on density functional theory authenticated the efficient sensing properties of Zn(BDC) MOF towards TNT. Furthermore, the promising response of the sensors in real sample matrices (tap water and wastewater) was demonstrated, opening new avenues towards the real-time detection of TNT in real environmental samples.